Geodemography as a component of population geography - A. Hetmanenko; V. Khomutov; O. Nikolaieva; S. Kudelina (Kazimierz Wielki University, 2023)
The article considers in detail the stages of formation and establishment of geodemography as a modern scientific direction of population geography. At the first stage, the central place in the system of knowledge about population belongs to demography. At the second stage, the interaction of demography with neighboring sciences, in particular with geography, is strengthened. At their junction, a new discipline is being formed - the geography of the population. At the third stage, a new direction of population geography is formed, focused on the study of regional differeces in population and settlement, and the development of regional demographic policy, which we call geodemography.